2015
DOI: 10.1111/jmp.12188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of putative mucosal SHIV susceptibility factors during repeated DMPA treatments in pigtail macaques

Abstract: All animals showed temporal vaginal epithelial thinning with loss of the non-nucleated layer, and vaginal pH changes post-DMPA injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 24 publications
6
23
1
Order By: Relevance
“…We determined resulting blood MPA levels over time, and their effectiveness in suppressing ovulation, their ability to induce thinning of the vaginal epithelium, and their effects on other putative HIV susceptibility factors. We showed that a low, monthly DMPA dose of 1.5 mg/kg can achieve suppression of ovulation over two months 18 , while it also achieves constantly detectable MPA levels, and is associated with significant vaginal epithelial thinning. Other slightly lower or higher doses were also associated with changes in these parameters 16-18 .…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…We determined resulting blood MPA levels over time, and their effectiveness in suppressing ovulation, their ability to induce thinning of the vaginal epithelium, and their effects on other putative HIV susceptibility factors. We showed that a low, monthly DMPA dose of 1.5 mg/kg can achieve suppression of ovulation over two months 18 , while it also achieves constantly detectable MPA levels, and is associated with significant vaginal epithelial thinning. Other slightly lower or higher doses were also associated with changes in these parameters 16-18 .…”
Section: Introductionmentioning
confidence: 84%
“…We showed that a low, monthly DMPA dose of 1.5 mg/kg can achieve suppression of ovulation over two months 18 , while it also achieves constantly detectable MPA levels, and is associated with significant vaginal epithelial thinning. Other slightly lower or higher doses were also associated with changes in these parameters 16-18 . In summary, we selected 1.5 kg/mg DMPA given monthly for our current study.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations